A Hydrogen Bonds-Crosslinked Hydrogels With Self-Healing and Adhesive Properties for Hemostatic - Han Yu; Han Yu; Han Yu; Qiaohong Xiao; Guilin Qi; Feixiang Chen; Biyue Tu; Suo Zhang; Yinping Li; Yun Chen; Hui Yu; Peng Duan (Frontiers in Bioengineering and Biotechnology, 2022)
Hydrogels with adhesive properties have the potential for rapid haemostasis and wound healing in uncontrolled non-pressurized surface bleeding. Herein, a typical hydrogen bond-crosslinked hydrogel with the above functions was constructed by directly mixing solutions of humic acid (HA) and polyvinylpyrrolidone (PVP), in which the HA worked as a crosslinking agent to form hydrogen bonds with the PVP. By altering the concentration of HA, a cluster of stable and uniform hydrogels were prepared within 10 s. The dynamic and reversible nature of the hydrogen bonds gave the HA/PVP complex (HPC) hydrogels injectability and good flexibility, as well as a self-healing ability. Moreover, the numerous functional groups in the hydrogels enhanced the cohesion strength and interaction on the interface between the hydrogel and the substrate, endowing them with good adhesion properties. The unique chemical composition and cross-linking mechanism gave the HPC hydrogel good biocompatibility. Taking advantage of all these features, the HPC hydrogels obtained in this work were broadly applied as haemostatic agents and showed a good therapeutic effect. This work might lead to an improvement in the development of multifunctional non-covalent hydrogels for application to biomaterials.